Experimental investigation of design parameters of temperature controlled semi-active shock absorber under different currents and velocities. Issue 5 (3rd September 2019) - Parlak, Zekeriya; Söylemez, M. Ertürk
Abstract: The effectiveness of the design parameters that affect the performance of semi-active shock absorber with magnetorheological (MR) fluid varies with the current excitation and damping velocity. Temperature has a very important effect on the performance of MR shock absorbers. In this study, the design parameters of a temperature-controlled MR shock absorber are evaluated under different current excitations and velocities. The manufactured dampers are tested at different current excitations and velocities. The effective levels of the parameters are determined according to the damping force and dynamic range. The expected performances of the best designs for MR shock absorbers and the effect of each design parameter on the performance are statistically calculated according to the different currents and velocities. The results show that the damping force decreased by 24.6% with varying temperature. The effect of the gap width decreased by 48.33% and the effect of the active length and radius of the piston core increased by 24.71 and 25.97%, respectively, when the current excitation changed from 0.2 to 1.8 A. The effect of the gap width increased by 2.56%, while the active length decreased by 4.12% at different velocities.